Open Science at the University of Toronto - Madelin Burt-D'Agnillo; Mindy Thuna (Partnership: The Canadian Journal of Library and Information Practice and Research)
Objective: The impetus for this project is to begin to understand open science practices and obstacles at the XXX. This project uses open-ended questions to understand the ways in which university-affiliated individuals learn about, think about, and interact with open science. The goal of this study is to showcase the complexity and diversity of activity and challenges in this domain to help determine how best to move open science forward.